Current Issues on TESOL Field in EFL Context - Nurmala Elmin Simbolon (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2012)
This article discusses several issues raised in TESOL field range from the variety of English to the technology application in language teaching. The term of English as an International Language, or EIL has been growing in TESOL field. And then, the issue about teaching focus is still fresh to discuss. The variety of cultures using English has stirred the language teaching to focus on the language use instead of the language form. Finally, technology implication such as online learning in TESOL classrooms is now increasing. To sum up, the issues link much with the importance of intercultural competence in second language teaching; therefore, some adaptations to the ELT teaching method in EFL context such as in Indonesia need to be adopted.